Pelaksanaan Manajemen Sarana Dan Prasarana Dalam Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Putri Wulandari Karimah; Sutarjo Sutarjo; Lilis Karyawati (Jurnal Ilmiah Wahana Pendidikan, 2022)
Motivation is very important in the learning process. With motivation students and teachers will be easier to achieve learning goals. Learning motivation is formulated as encouragement, both internal and external factors. One of the motivations from outside is the availability of educational facilities and infrastructure. Therefore, good management of facilities and infrastructure is needed to be able to provide comfort in the learning process. The purpose of this study was to determine, describe and analyze the implementation of the procurement and maintenance of school facilities and infrastructure. This study uses a literature review on the concept of facilities and infrastructure management. The result of this research is that the management of facilities and infrastructure is one of the factors that can affect students' learning motivation.